1998
DOI: 10.1021/jf980468+
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Storage of Green Robusta Coffee under Tropical Conditions and Its Impact on Raw Material Quality and Ochratoxin A Content

Abstract: Green Robusta coffee was stored in silos for 8 months under industrial conditions in Thailand, and subjected to air-conditioning, aeration, and nonaeration, and compared to bag storage under ambient conditions. Air-conditioning clearly reduced the relative humidity (RH) of the silo atmosphere and the moisture content (MC) and the water activity (a w) of green coffee. Overall storage behavior was better for coffee in the aerated silo (RH = 68%; MC = 13.0%; a w = 0.69) than for coffee stored in bags (RH = 81%; M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 8 publications
2
55
1
6
Order By: Relevance
“…Therefore methods which use fermentation takes long time between 16 and 20 h before coffee parchment is subjected to drying. The level of the moisture content is important for preservation of coffee quality because higher moisture levels than 12% will favour the growth of moulds and cause off flavours affecting the taste qualities of coffee (Bucheli et al, 1998;Ismail et al, 2013). Regarding the mass of coffee samples, disc pulper method showed a significantly lower value than the eco-pulper method during season 1 harvest (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore methods which use fermentation takes long time between 16 and 20 h before coffee parchment is subjected to drying. The level of the moisture content is important for preservation of coffee quality because higher moisture levels than 12% will favour the growth of moulds and cause off flavours affecting the taste qualities of coffee (Bucheli et al, 1998;Ismail et al, 2013). Regarding the mass of coffee samples, disc pulper method showed a significantly lower value than the eco-pulper method during season 1 harvest (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A. ochraceus was found only at the 20 th day of fermentation, not being detected during storage. Aspergillus species have been frequently reported in beans and stored grains of coffee (3,4,6,7,17,32,33,35,37). Besides compromising the quality of the product, the presence of Aspergillus may affect their safety due to production of secondary metabolites toxic to man and animals (mycotoxins).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria, yeasts and filamentous fungi have been already reported in the pulp and beans of coffee processed in Brazil, India, Hawaii, Congo, Argentina, Colombia, Costa Rica, Ethiopia and Mexico (2,12,30,32). Filamentous fungi predominate at the end of the processing and during storage, and may affect the quality and safety of the final product due to production of mycotoxins (4,6,34,35). Several studies have reported the occurrence of toxinproducing fungi and ochratoxin in green coffee beans (4,18,20,26,28).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of OTA in coffee is not known. Bucheli et al (1998) studied the accumulation of OTA during storage of green coffee beans and found no growth of OTA-producing fungi and no consistent production of OTA at different storage conditions. It appeared that accumulation of OTA in coffee beans occurred before storage and it was suggested to be linked mainly to post-harvest conditions of coffee processing (Bucheli et al, 1998(Bucheli et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Bucheli et al (1998) studied the accumulation of OTA during storage of green coffee beans and found no growth of OTA-producing fungi and no consistent production of OTA at different storage conditions. It appeared that accumulation of OTA in coffee beans occurred before storage and it was suggested to be linked mainly to post-harvest conditions of coffee processing (Bucheli et al, 1998(Bucheli et al, , 2000. However, for Brazilian coffee, it was found that the highest levels of contamination with OTA and OTA-producing fungi occurred in coffee beans during drying and storage (Taniwaki et al, 2003).…”
Section: Introductionmentioning
confidence: 99%